Method of Achieving the Least Loss of Information in an Asynchronous Binary Single-Photon Communication Channel with a Receiver Based on a Photon Counter - A. M. Timofeev (Приборы и методы измерений)
Receiving modules of single-photon communication systems should provide the smallest loss of transmitted information when measuring low-power optical signals. In this regard, it is advisable to use photon counters. They are the most highly sensitive, but characterized by data recording errors. The aim of this work was to develop a method for determining the intensity of recorded optical signal in a singlephoton communication channel with a receiving module based on a photon counter, which ensures the least probability of erroneous registration of transmitted binary symbols.Methods of achieving the least loss of information in asynchronous photon binary communication channel with a receiver-based photon counter has been developed. A device for implementing this methods has been created. The method is based on using the statistical distribution of the mixture of the number of dark and signal pulses received at the output of the photon counter when registering binary symbols "0" Pst 0 (N ) and symbols "1" Pst 1 (N ). The essence of the method consists in determining the intensities of optical signals for transmitting binary symbols ("0" and "1") and threshold levels of the pulses N1 and N2 registered at the output of the photon counter. The method allows to determine the lower and upper threshold levels of recorded pulses and the intensity of optical signals in the transmission of binary data. Moreover, the probability of erroneous registration of binary symbols is minimal.